Performance of Hybrid Castellated Beams: Prediction Using Finite Element Modeling - Salah, W. A. (Engineering, Technology & Applied Science Research, 2022)
In the current study, the up to failure behavior of the Hybrid Castellated Beams (HCBs) is predicted with the use of a developed Finite Element (FE) model. Both material and geometric nonlinearities are considered in the numerical simulations. The accuracy of the FE model was validated using the experimental test results presented in the literature. The results of the FE analysis had a close agreement with the experimental work in predicting the failure load and failure mode pattern. A parametric study was conducted to investigate the influence of some parameters on HCBs’ ultimate strength. These parameters included slenderness of compression flange, beam span-to-depth ratio, and laterally unbraced length of compression flange. A design formula is proposed to estimate the inelastic lateral-distortional strength of both homogeneous and hybrid material castellated beams.